2019
DOI: 10.2147/cmar.s211363
|View full text |Cite
|
Sign up to set email alerts
|

<p>The CRP/Albumin Ratio Predicts Survival And Monitors Chemotherapeutic Effectiveness In Patients With Advanced Pancreatic Cancer</p>

Abstract: The CRP/albumin (Alb) ratio, a recently reported predictor, has shown value for prognosis in various human cancers. This study aimed to determine the prognostic value of baseline CRP/Alb and to explore the relevance between postchemotherapy CRP/Alb and the efficacy of chemotherapy in advanced pancreatic cancer patients. Patients and methods: Five hundred and ninety-five patients diagnosed with locally advanced or metastatic adenocarcinoma of the pancreas were enrolled. Cutoff Finder was used to calculate the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…Seventeen studies were excluded after full-text review for insufficient data (n = 13), recruiting overlapping patients (n = 2), not focusing on pancreatic cancer (n = 1), and lack of pretreatment CAR measurement. Finally, the meta-analysis included a total of 11 studies 14 -24 comprising 2271 patients. The baseline characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seventeen studies were excluded after full-text review for insufficient data (n = 13), recruiting overlapping patients (n = 2), not focusing on pancreatic cancer (n = 1), and lack of pretreatment CAR measurement. Finally, the meta-analysis included a total of 11 studies 14 -24 comprising 2271 patients. The baseline characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The baseline characteristics of the included studies are shown in Table 1. The studies were published from 2016 to 2019 from 5 countries, including Japan (n ¼ 4), 17,19,20,23 China (n ¼ 3), 15,16,22 Korea (n ¼ 2), 14,21 Italy (n ¼ 1), 18 and Austria (n ¼ 1). 24 The sample sizes ranged from 43 to 595, with a median of 188.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…An increased CAR indicates a poor clinical prognosis in patients undergoing percutaneous coronary intervention [31]. Recent studies showed that the CAR was predictive of disease progression and mortality in patients with gastric cancer, pancreatic cancer and non-small-cell lung cancer [13,22,32,33]. The results of the study by Miyamoto et al showed that the CAR was an independent factor that was predictive of two-week survival; in particular, the CAR is a useful tool for predicting survival times in end-stage patients with or without cancer [34].…”
Section: Discussionmentioning
confidence: 99%